Impact of Stock Split on Stock Liquidity of the Companies Listed on NSE and BSE - YASHIKA GARG, KANIKA SACHDEVA, PANKAJ NATU (Journal of Informatics Education and Research, 2025)
The aim of study is to find out difference in levels of stock liquidity before and after stock split. The study aims to analyse all the companies that have carried out stock split in Indian stock markets- BSE and NSE between the period 1st April 2019- 31st March 2022. Purposive sampling method is used to get required data. Out of all the companies which performed stock split between the mentioned period (166 companies), all the companies carrying out forward stock split (119 companies) were chosen to carry out the research. With the use of Wilcoxon signed rank test results are obtained to find out difference in stock liquidity data before and after split within the time frame of 30 days. Since the value of p obtained is less than the conventional significance level of 0.05 (indicated as "<.001"), we reject the test null hypothesis which states that there is no difference between the paired observations and accept the alternate hypothesis which concludes that there is significant impact of stock split on stock liquidity.